Energy sustainability with solar panels and their economic-social relationship in the uncertainty for the regional development of Mexico - Ramos Sánchez, Jesús Ricardo; Chávez Rivera, Rubén; Alcaraz Vera, Jorge Víctor (Unidad Editorial UPTC, 2021)
The global trend in generating alternative ways to access sustainable and environmentally friendly economies has gained special importance, as there are other ways of obtaining resources, satisfying needs, and the same generation of energy without the absolute dependence on fossil fuels. The global trend shows diverse mechanisms of energy production, however, the difficulty in quantifying multifactor systems in socio-economic standards is complex and even more so, its effect on regional development. In the case study, it appears that 25% of users do not achieve significant sustainable savings with the use of photovoltaic cells in homes in extreme weather. Through fuzzy relationships, critical factors about human behaviour are identified. The critical factors are obtained from the factor analysis, it allows justifying the latent variables with the critical factors based on the perception of the respondents, and these variables are the basis for influencing the causal relationships that affect with Fuzzy Cognitive Maps to know the sustainability or unsustainability energetic. Keywords: control, renewable energy, measurement, solar panels, sustainability. JEL codes: D14, D61, I31, O33, 035, P18, P28 Received: 06/12/2020. Accepted: 25/07/2021. Published: 01/12/2021.